Changes in Therapist Actions During a Novel Pediatric Physical Therapy Program: Successes and Challenges. Issue 3 (July 2018) - Akhbari Ziegler, Schirin; Dirks, Tineke; Reinders-Messelink, Heleen A.; Meichtry, André; Hadders-Algra, Mijna
Abstract : Purpose: To monitor changes in time spent on pediatric physical therapy actions during a COP ing With and CA ring for Infants With Special Needs (COPCA) course. Methods: Data were collected before (T0), during, and after (T3) the course, which was attended by 15 Swiss physical therapists. Four treatment sessions of each therapist were video recorded and analyzed with the Groningen Observation Protocol 2.0, allowing for quantification of relative duration of therapeutic actions. Results: Between T0 and T3, time spent on caregiver coaching and hands-off approaches significantly increased. Conclusions: The shift from caregiver trainer to family coach and the increasing hands-off techniques represent successful changes in various domains of behavior. The moderate changes in hands-off approaches suggest that changing habits requires specific attention. The COPCA course will be adapted accordingly. Abstract : Supplemental Digital Content is Available in the Text.This study monitored changes in time spent on pediatric physical therapy actions during a 'COPing with and CAring for Infants with special Needs' course.